2003
DOI: 10.1046/j.1365-2559.2003.01549.x
|View full text |Cite
|
Sign up to set email alerts
|

H‐caldesmon expression in myofibroblastoma of the breast: evidence supporting the distinction from leiomyoma

Abstract: Our results, indicating that smooth muscle differentiation occurs in a minority of the myofibroblastoma cells exclusively in half of the analysed cases, support the separation of myofibroblastoma from leiomyoma. The detection of smooth muscle cells in breast myofibroblastoma is easily explained if we postulate its histogenesis from the CD34+ fibroblasts of mammary stroma capable of multidirectional mesenchymal differentiation, including smooth muscle. We recommend retention of the term myofibroblastoma for all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 25 publications
0
32
0
Order By: Relevance
“…In addition, calponin can be inconsistently encountered focally in a host of other spindle cell tumors, including malignant peripheral nerve sheath tumor, solitary fibrous tumor, dermatofibrosarcoma protuberans, fibrosarcoma, and carsinosarcoma [27,28]. Recently, h-caldesmon has been proposed as a useful marker for distinguishing smooth muscle tumors from myofibroblastic tumors, because h-caldesmon is negative in myofibroblastic lesions, such as fibromatosis [7,29] and nodular fasciitis [29]. Moreover, cases of IMT [7,9,11] and LGMS [6] were also reported to be negative for h-caldesmon.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, calponin can be inconsistently encountered focally in a host of other spindle cell tumors, including malignant peripheral nerve sheath tumor, solitary fibrous tumor, dermatofibrosarcoma protuberans, fibrosarcoma, and carsinosarcoma [27,28]. Recently, h-caldesmon has been proposed as a useful marker for distinguishing smooth muscle tumors from myofibroblastic tumors, because h-caldesmon is negative in myofibroblastic lesions, such as fibromatosis [7,29] and nodular fasciitis [29]. Moreover, cases of IMT [7,9,11] and LGMS [6] were also reported to be negative for h-caldesmon.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, h-caldesmon has been proposed as a useful marker for distinguishing smooth muscle tumors from myofibroblastic tumors, because h-caldesmon is negative in myofibroblastic lesions, such as fibromatosis [7,29] and nodular fasciitis [29]. Moreover, cases of IMT [7,9,11] and LGMS [6] were also reported to be negative for h-caldesmon. We have extended these observations, finding no h-caldesmon expression in all our cases of IMT and LGMS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…46 The clinical use of h-CD has been addressed mainly in differentiating smooth muscle tumors (eg, leiomyomas and leiomyosarcomas) from other soft tissue tumors with smooth muscle cell-like differentiation, including tumors of myofibroblastic and fibroblastic origin. 10,15,27,29,32,39,47,48 In addition, we recently demonstrated that h-CD is also a highly specific and sensitive positive marker of cells with mesothelial differentiation and therefore a new marker for the positive diagnosis of epithelioid mesothelioma. 14 D2-40 is a recently developed monoclonal antibody that reacts with a 40-kD oncofetal antigen, known as M2A antigen, expressed in fetal testis and in germ-cell tumors.…”
mentioning
confidence: 99%
“…6-9). 18 The malignant variants of spindle cell presents typically greater cell density, marked nuclear pleomorphism, high mitotic activity with atypical mitotic figures. It has been extensively debated whether solitary fibrous tumor and myofibroblastoma of the breast should be considered as two distinct lesions.…”
Section: Case Presentationmentioning
confidence: 99%